Foreign Language Teaching Methodology as An Independent Theoretical and Applied Science - Shadmanbekova Kamola Abdulazizovna (Genius Journals, 2021)
The article discusses foreign language teaching methodology as an independent theoretical and applied science. The study of foreign languages in modern society is becoming an inseparable component of the professional training of specialists of various profiles, and the successful solution of professional growth issues and the expansion of contacts with foreign partners largely depend on the quality of their language training
Keywords: General methodology; basic concepts; process; goals